A Case of Old Calcifying Epithelioma Processed Symptomless over 40 Years - Shinji Yamaguchi; Madoka Inui; Takashi Takeoka; Kenya Okumura; Toshiro Tagawa (Hindawi Limited, 2013)
Calcifying epithelioma, a benign tumor derived from the hair apparatus and consisted of hair matrix cells, is relatively prevalent in females. We report a case of right preauricular calcifying epithelioma that was incidentally detected at the examination of multiple facial fractures and became an old lesion without symptoms for 40 years. The patient who was a 42-year-old male visited our department for the first time in October 2011 with a chief complaint of multiple facial fractures. Radiographic imaging demonstrated fracture lines at the anterior and posterior walls of the left maxillary sinus and zygomatic arch and revealed a mass at a right preauricular area. The extraction was performed under general anaesthesia. No recurrence has been observed 15 months after surgery. We also reviewed the literature of calcifying epithelioma.